(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article is devoted to the study of the phenomenon of synonymy in adjective phraseological units. Concepts such as phraseological synonymy are considered, phraseological units and variants are analyzed, the classification of adjectives of phraseological units is given in accordance with their attribution to synonymic paradigms and series.